2016
DOI: 10.3389/fonc.2016.00175
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair and Cytokines: TGF-β, IL-6, and Thrombopoietin as Different Biomarkers of Radioresistance

Abstract: Double strand breaks (DSBs) induced by radiotherapy are highly cytotoxic lesions, leading to chromosomal aberrations and cell death. Ataxia-telangiectasia-mutated (ATM)-dependent DNA-damage response, non-homologous end joining, and homologous recombination pathways coordinately contribute to repairing DSBs in higher eukaryotes. It is known that the expression of DSB repair genes is increased in tumors, which is one of the main reasons for radioresistance. The inhibition of DSB repair pathways may be useful to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 70 publications
(125 reference statements)
1
53
0
Order By: Relevance
“…The malignant tumor microenvironment (TME) governs tumor progression [1], metastasis and recurrence. The cytokines, chemokines and/or growth factors produced by cancerous and stromal cells can cause tumor aggressiveness and/or therapeutic resistance that determine the overall and recurrence-free survival rates of patients [2][3][4][5]. Tumor-associated macrophages (TAMs) undergo M1 or M2 macrophage polarization in response to different stimuli [6].…”
Section: Introductionmentioning
confidence: 99%
“…The malignant tumor microenvironment (TME) governs tumor progression [1], metastasis and recurrence. The cytokines, chemokines and/or growth factors produced by cancerous and stromal cells can cause tumor aggressiveness and/or therapeutic resistance that determine the overall and recurrence-free survival rates of patients [2][3][4][5]. Tumor-associated macrophages (TAMs) undergo M1 or M2 macrophage polarization in response to different stimuli [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, TGF‐β, which is abundantly present in many tumors, has been demonstrated to increase the numbers of CSCs via cancer cell dedifferentiation . It is not without reason that both IL‐6 and TGF‐β have recently been defined as biomarkers of tumor malignity and radioresistance . Therefore, it has been suggested that CSCs could be indirectly eradicated by disrupting their relationship with the TME.…”
mentioning
confidence: 99%
“…Previous study has investigated the effect of individual cytokines in the tumor microenvironment on tumor radiation resistance (15). In the present study, enhanced radioresistance of H460 cells was examined in the presence of a milieu of autocrine factors, and their effects were indicated to be independent of the presence of exosomes.…”
Section: Discussionmentioning
confidence: 88%
“…Vascular endothelial Autocrine secretions enhance radioresistance in an exosome-independent manner in NSCLC cells growth factor (VEGF) has been documented to promote malignant astrocytoma growth and radioresistance via VEGF receptor 2 (also known as kinase insert domain receptor) and co-activation of c-Raf/mitogen-activated protein kinase, phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt and phospholipase C/protein kinase C signaling pathways (14). In another study, the ability of cytokines to support DNA repair pathways and an ATM serine/threonine kinase-dependent DNA response were observed (15). Additionally, cell secreted exosomes, which represent extracellular microvesicles with diameters ranging from 30 to 100 nm that contain an abundance of proteins, messenger RNAs, microRNAs, and long non-coding RNAs, may contribute to tumor metastasis, angiogenesis and migration via autocrine/paracrine signaling (16).…”
Section: Introductionmentioning
confidence: 98%